the ANALYSIS OF TA'AWUN FUND MANAGEMENT FOR FINANCING MEMBERS WHO PASS AWAY BEFORE MATURITY AT KSPPS BMT AL HIKMAH SEMESTA KALINYAMATAN BRANCH ACCORDING TO THE PERSPECTIVE OF MUAMALAH MALIYAH - Khasanah, Miftakhul; Mubarok, Ahmad Fauzan; Utami, Cahyaning Budi (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This research aims to determine the handling of death financing before maturity from the perspective of muamalah maliyah. Handling financing for members who pass away before the due date is an important matter that requires attention. This is because Islamic financial institutions face risks when members are unable to meet their installment payment obligations due to death. This research uses a qualitative approach. Researchers used three data collection techniques: interviews, literature review, and documentation. Handling financing for death before maturity from the perspective of muamalah maliyah is permissible thru the mechanism of ta'awun funds. This cooperative fund serves to pay off debts left by members without burdening their heirs, in line with the principles of Sharia that emphasize the importance of mutual assistance and care for others. The existence of these funds not only eases the burden on the bereaved families but also reflects the value of justice in Islamic teachings. The importance of applying the principles of financial transactions in every financing transaction. By prioritizing the principles of mutual assistance and care among members.